Key technologies and development trends of intelligent customer service for operators - Xiaoliang MA; Ying LIU; Dequan DU; Lingling AN (Dianxin kexue)
The technology development trend of intelligent customer service for operators was discussed, and automatic speech recognition (ASR) transcription error correction technology, semantic extraction technology, encrypted database, and agent access control technology were introduced.Two different research directions of error detection and automatic error correction for speech recognition were analyzed, two directions of supervised learning and unsupervised learning were discussed, and big data encryption and agent access control technologies were introduced.At the same time, the technical directions of multimodal interaction technology, intelligent recommendation technology and disabled-oriented services were prospected.In conclusion, the development and innovation of intelligent customer service technology will bring a more efficient and convenient service experience to the communication industry and strongly promote the progress of the industry service level.